Study on surface-wave tomography in Abaga volcanic area, Inner Mongolia - Hou, Jie; Wu, Qingju; Yu, Daxin; Ye, Qingdong; Zhang, Ruiqing (Frontiers in Earth Science, 2023)
In this paper, the 3-D S-wave velocity structure of the crust and upper mantle in the Abaga volcanic area of Inner Mongolia was inverted by using the surface-wave tomography method, with a resolution of 0.5°×0.5°. For the first time, the vertical continuous data recorded by 36 and 25 broadband mobile seismic stations in Abaga volcanic area from October 2012 to May 2015 (NM array) and October 2017 to October 2018 (AB array) were adopted together. The results showed that there was a significant high velocity anomaly structure in the upper mantle at 80 140 km depth in the Abaga volcanic area, and there was a significant low velocity anomaly structure above the high velocity anomaly, which reflected that lithospheric delamination may occurr in the Abaga volcanic area. The overlying NW-SE low-velocity anomaly extended northwest to the boundary of the study area, then to the South Gobi of the Mongolian Plateau; spread southeast to the crustal thinning area and the exposed position of the Abaga volcanic group on the surface. According to the analysis of previous research results, it speculated that this low velocity anomaly may reflect the upwelling asthenosphere, suggesting that the Abaga volcanic group and the South Gobi of the Mongolian Plateau were homologous in depth. Also there was a NEE-SWW low velocity anomaly in the depth range of 40-150 km in the east of Honggeertu volcano, which implied the upwelling of local mantle material formed by the lithospheric delamination in Songliao basin.